The Gonium pectorale genome demonstrates co-option of cell cycle regulation during the evolution of multicellularity - Hanschen, E. R.; Marriage, Tara N.; Ferris, P. J.; Hamaji, T.; Toyoda, A.; Fujiyama, A.; Neme, R.; Noguchi, H.; Minakuchi, Y.; Suzuki, M.; Kawai-Toyooka, H.; Smith, D. R.; et al. (My University, 2016)
The transition to multicellularity has occurred numerous times in all domains of life, yet its initial steps are poorly understood. The volvocine green algae are a tractable system for understanding the genetic basis of multicellularity including the initial formation of cooperative cell groups. Here we report the genome sequence of the undifferentiated colonial alga, Gonium pectorale, where group formation evolved by co-option of the retinoblastoma cell cycle regulatory pathway. Significantly, expression of the Gonium retinoblastoma cell cycle regulator in unicellular Chlamydomonas causes it to become colonial. The presence of these changes in undifferentiated Gonium indicates extensive group-level adaptation during the initial step in the evolution of multicellularity. These results emphasize an early and formative step in the evolution of multicellularity, the evolution of cell cycle regulation, one that may shed light on the evolutionary history of other multicellular innovations and evolutionary transitions.
Citation: Hanschen, E. R., Marriage, T. N., Ferris, P. J., Hamaji, T., Toyoda, A., Fujiyama, A., . . . Olson, B. (2016). The Gonium pectorale genome demonstrates co-option of cell cycle regulation during the evolution of multicellularity. Nature Communications, 7, 10. doi:10.1038/ncomms11370
Additional Authors: Anderson, J.;Bakaric, R.;Luria, V.;Karger, A.;Kirschner, M. W.;Durand, P. M.;Michod, R. E.;Nozaki, H.
Keywords: Retinoblastoma Tumor-Suppressor; Transcription Factor Database; Protein; Families Database; Phylogenetic Analysis; Extracellular-Matrix